Parafasias fonológicas más frecuentes en los estudiantes de segundo año de Idiomas: inglés-alemán de la UNT, año 2017 - Huamán Chuquipoma, Lizbeth Jobita (2019)
This present research study entitled "Most frequent phonological paraphasias in second year students of Languages: English-German of the UNT, year 2017", had as a main objective to determine the most frequent phonological paraphasias in the students of the second year of the professional career of Languages: English-German of the National University of Trujillo in 2017. At the same time, it sought to identify the words of the English language that cause more phonological paraphasias in the second-year students of the professional career of Languages: English - German of the National University of Trujillo in the year 2017. Also, this research work sought to classify the most frequent phonological paraphasias in the students of the second year of the professional career of Languages: English-German of the National University of Trujillo in 2017, in sublevels. To achieve these objectives, two instruments for data collection were applied: an observation guide, where the incidences of seven classroom observations of the German I course and a reading, where the students were asked to read aloud, and thus evaluate the oral production. The population consisted of 73 students of the professional career of Languages: English - German of the National University of Trujillo in 2017 and the sample, by 24 students, which had the following characteristic: a mixed group of students of the second academic year. The sample was chosen in a non-probabilistic way, using the criterion of intentional selection, due to these students studied German for the first time. With the help of a simple tabulation was found the frequency of repetition of words that originated phonological paraphasias in the German students of the second year of the professional career of Languages: English - German of the National University of Trujillo in the year 2017. ix At the end of this investigation, it was determined that the syllabic substitution and the accentuation in the penultimate syllable of a word were the most frequent phonological paraphasias in German students of the second year of the professional career of Languages of the National University of Trujillo in 2017. It is hoped that the present work will constitute a documentary source for future research on the subject.